Underwater Image Enhancement using Image Processing Techniques: A Review - Wany, Arpit; Rathore, Yogesh (International Journal of Computer Sciences and Engineering, 2021)
While capturing underwater image there are lot of imposed due to low light, light variation, poor visibility. Photography is about light, but since water has an a lot more prominent density than air — around 800 times more noteworthy — not all orientation of light travel similarly well inside it. This implies as we go down into deep water, we lose the shades of the range one by one. This is the reason submerged photographs lose all the red and orange hues even at a genuinely shallow profundity and appear to be increasingly more blue as we go deep in water, henceforth captured image need enhancement. It’s a vital research area. We proposed an effective technique so that we can improve the images which are captured underwater and degraded because of the medium scattering and absorption. Our technique is a single image approach that does not require specialized hardware or knowledge about the underwater conditions or scene structure. It is build on the blending of two images that are directly derived from a color compensated and white-balanced version of the original degraded image. The two images to fusion, as well as their associated weight maps, are defined to promote the transfer of edges and color contrast to the output image. To avoid that sharp weight map transitions builds artifacts in the low frequency components of the reconstructed image, we also conform a multi scale fusion strategy. Our extensive qualitative and quantitative analysis reveals that our enhanced images and videos are characterized by better exposedness of the dark regions, enhanced global contrast, and edges sharpness. Our validation also shows that our algorithm is reasonably independent of the camera settings, and enhance the accuracy of several image processing applications, such as image processing and key-point matching.